Shifting Nicaraguan Mediascapes Authoritarianism and the Struggle for Social Justice - Cupples, Julie (SpringerBriefs in Latin American Studies, 2018)
This book explores the mediated struggles for autonomy, land rights and social justice in a context of growing authoritarianism and persistent coloniality in Nicaragua. To do so, it draws on in-depth fieldwork, analysis of media texts, and decolonial and other cultural theories. There are two main threats to the authoritarian rule of the Nicaraguan government led by Daniel Ortega: the first is the Managua-based NGO and civil society sector led largely by educated dissident Sandinistas, and the second is the escalating struggle for autonomy and land rights being fought by Nicaragua's indigenous and Afro-descended inhabitants on the country's Caribbean coast. In order to confront these threats and, it seems, secure indefinite political tenure, the government engages in a set of centralizing and anti-democratic political strategies characterized by secrecy, institutional power grabs, highly suspect electoral practices, clientelistic anti-poverty programmes, and the control through purchase or co-optation of much of the nation's media. The social movements that threaten Ortega's rule are however operating through dispersed and topological modalities of power and the creative use of emergent spaces for the circulation of counter-discourses and counter-narratives within a rapidly transforming media environment. The primary response to these mediated tactics is a politics of silence and a refusal to acknowledge or respond to the political claims made by social movements. In the current conjuncture, the authors identify a struggle for hegemony whose strategies and tactics include the citizenship-stripping activities of the state and the citizenship-claiming activities of black, indigenous and dissident actors and activists. This struggle plays out in part through the mediated circulation and counter-circulation of discourses and the infrastructural dynamics of media convergence.